Occurrence and characteristics of microplastics pollution in tropical agricultural soils in Klang Valley, Malaysia - Shanmugam, Shyamala Devi; Praveena, Sarva Mangala; Wahid, Samsuri Abdul; Liew, Josephine Ying Chyi (Springer, 2024)
Presently, microplastic pollution has emerged as a growing environmental risk around the world. Nevertheless, knowledge of the occurrence and characteristics of microplastics in tropical agricultural soil is limited. This study investigated the pollution of surface soil microplastics in two agricultural farms located at Klang Valley, Malaysia. An extraction method based on density separation by using saturated extraction solution (sodium sulfate, ρ = 2 g cm−3 and sucrose, ρ = 1.59 g cm−3 with a ratio 1:1, v/v) was carried out. The study revealed the mean particle size of soil microplastics with 3260.76 ± 880.38 μm in farm A and 2822.31 ± 408.48 μm in farm B. The dominant types of soil microplastics were fragments and films with major colors of white (59) and transparent (28) in farm A, while black (52) and white (37.6) in farm B. Representatives of soil microplastics detected polymers of polyvinyl chloride (PVC), high density polyethylene (HDPE), polycarbonate (PC), and polystyrene (PS). The sources of plastic products were black and white plastic pipes, black plastic films for vegetation, fertilizer bottles, plastic water containers and polystyrene storage boxes, and the breakdown processes, contributed to the microplastic pollution in these farms. The outcomes of this study will establish a better understanding of microplastic pollution in tropical agricultural soil in the Southeast Asian region. The findings would be beneficial as supportive reference for the endeavor to reduce microplastic pollution in agricultural soil. © 2024, The Author(s), under exclusive licence to Springer Nature Switzerland AG.